Review of the Monograph: Serkov P. P. Legal Relationship (Theory and Practice of Modern Legal Policy). Moscow: Norma, 2023. 1544 p. - N. N. Tsukanov (Сибирское юридическое обозрение, 2023)
The presented review gives a general assessment of the monograph by the famous Russian scholar, a specialist with significant practical experience, Doctor of Legal Sciences, Professor Petr Pavlovich Serkov. The philosophical and legal orientation of the study is stated, the key provisions and conclusions of the author are evaluated, the prospects for further scientific and practical use of the results are noted. In the first part of the review, the specifics of the subject of research determined by P. P. Serkov are considered. It is noted that the latter is many times wider than the subject of legal relations in the usual sense for a modern lawyer. The title of the monograph is due to the fact that the author of the work gives this category a special place, recognizing it as the fundamental basis of the system of legal regulation. Attention is drawn to the breadth and diversity of the illustrative material, the originality of the methods used by the Author of setting research problems and formulating scientific questions, determining methods for solving them, choosing the form and style of presenting the results. Numerous references to the text of the monograph are given to substantiate the conclusions, and brief generalizations are formulated. The second section of the work is devoted to the style of presentation of scientific material, focuses on its influence on the perception of the text and its content. It is noted that this feature makes the text more vivid, figurative, but at the same time significantly complicates the work with it, makes it difficult to accurately understand the Author’s idea. The third section reflects the features of the structure of the work. The review draws attention to the non-standard approach of Petr P. Serkov to the naming and mutual arrangement of structural elements, to the intractability of certain scientific questions formulated by Petr P. Serkov. The method of argumentation used by the Author by means of references to the unprovenness of one or another thesis is especially noted. The controversial provisions of the monograph are noted. The reviewer does not share the Author’s skeptical attitude to the methodology of modern legal science, his opinion on the need to revise the role of the abstraction method in scientific legal research, on the place of legal relations in the structure of legal matter, and on a number of other scientific issues.